Intraspecific Variation for Leaf Physiological and Root Morphological Adaptation to Drought Stress in Alfalfa (Medicago sativa L.) - Prince, Silvas; Anower, Md Rokebul; Motes, Christy M.; Hernandez, Timothy D.; Liao, Fuqi; Putman, Laura; Mattson, Rob; Seethepalli, Anand; Shah, Kushendra; Komp, Michael; Mehta, Perdeep; York, Larry M.; et al. (Frontiers in Plant Science, 2022)
Drought stress reduces crop biomass yield and the profitability of rain-fed agricultural systems. Evaluation of populations or accessions adapted to diverse geographical and agro-climatic environments sheds light on beneficial plant responses to enhance and optimize yield in resource-limited environments. This study used the morphological and physiological characteristics of leaves and roots from two different alfalfa subspecies during progressive drought stress imposed on controlled and field conditions. Two different soils (Experiment 1 and 2) imposed water stress at different stress intensity and crop stages in the controlled environment. Algorithm-based image analysis of leaves and root systems revealed key morphological and physiological traits associated with biomass yield under stress. The M. sativa subspecies (ssp.) sativa population, PI478573, had smaller leaves and maintained higher chlorophyll content, leaf water potential, and osmotic potential under water stress. In contrast, M. sativa ssp. varia, PI502521 had larger leaves, a robust root system, and more biomass yield. In the field study, an unmanned aerial vehicle survey revealed PI502521 to have a higher normalized difference vegetation index (vegetation cover) throughout the cropping season, whereas PI478573 values were low during the hot summer and yielded low biomass in both irrigated and rainfed treatments. RhizoVision Explorer image analysis of excavated roots revealed a smaller diameter and narrow root angle as target traits to increase alfalfa biomass yield irrespective of water availability. Root architectural traits such as network area, solidity, volume, surface area, and maximum radius exhibited significant variation at the genotype level only under limited water availability. Different drought-adaptive strategies identified across subspecies population will benefit the plant under varying levels of water limitation and facilitate the development of alfalfa cultivars suitable across a broad range of growing conditions. The alleles from both subspecies will enable the development of drought-tolerant alfalfa with enhanced productivity under limited water availability.